1998
DOI: 10.1099/00221287-144-7-1895
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mutants deficient in acetyl-CoA synthetase and a possible regulator of acetate induction in Aspergillus niger

Abstract: Acetate-non-utilizing mutants in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In Rhodobacter sphaeroides, propionyl-CoA was found to inhibit pyruvate dehydrogenase (19), and in Escherichia coli, propionyl-CoA is a competitive inhibitor of citrate synthase (20). Support for the idea that propionyl-CoA is a problem for the cell was also obtained in Aspergillus niger, where experiments blocking propionyl-CoA formation relieved propionate sensitivity (21). However, recent experiments suggest that the inhibitory effects of propionate in A. niger may be caused by 2-methylcitrate accumulation (22).…”
mentioning
confidence: 52%
“…In Rhodobacter sphaeroides, propionyl-CoA was found to inhibit pyruvate dehydrogenase (19), and in Escherichia coli, propionyl-CoA is a competitive inhibitor of citrate synthase (20). Support for the idea that propionyl-CoA is a problem for the cell was also obtained in Aspergillus niger, where experiments blocking propionyl-CoA formation relieved propionate sensitivity (21). However, recent experiments suggest that the inhibitory effects of propionate in A. niger may be caused by 2-methylcitrate accumulation (22).…”
mentioning
confidence: 52%
“…It had previously been found that disruptants of acuB are able to grow on propionate but not on acetate as a sole carbon source (23,25). Moreover, it was observed that propionate interferes with sporulation and growth of strains able to use acetate (25).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was observed that propionate interferes with sporulation and growth of strains able to use acetate (25). Accordingly, since acuB-positive strains fail to sporulate on propionate medium, acuB⌬ strains can be identified simply as strains that sporulate on this medium.…”
Section: Resultsmentioning
confidence: 99%
“…In A. nidulans, A. niger and Coprinus cinereus conventional mutagenesis coupled with selection for either fluoroacetate or proprionate resistance resulted in the isolation of a number of acetate non-utilising mutants (Apirion 1965;Armitt et al 1976;Vousden and Casselton 1983;Sealy-Lewis 1994;Sealy-Lewis and Fairhurst 1998). Common classes amongst these mutants are the facB-like mutants, which typically show poor induction of a series of enzymes required for acetate utilisation (Hynes 1977;Maconochie et al 1992;Sealy-Lewis and Fairhurst 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Common classes amongst these mutants are the facB-like mutants, which typically show poor induction of a series of enzymes required for acetate utilisation (Hynes 1977;Maconochie et al 1992;Sealy-Lewis and Fairhurst 1998). The facB gene product has been established as a positively acting regulatory factor required for the induction of the genes of the glyoxylate cycle, as well as the metabolite-mobilising enzymes acetyl-CoA synthetase (facA) and acetamidase (amdS) (Katz and Hynes 1989;Todd et al 1998).…”
Section: Discussionmentioning
confidence: 99%